Enhanced Graphene Based Electronically Tunable Phase Shifter - Muhammad Yasir; Fabio Peinetti; Patrizia Savi (Micromachines, 2023)
In this work, an enhanced tunable microwave phase shifter is presented. The phase shifter consists of three short circuited stubs and a tapered line. The stubs are connected to graphene pads. Graphene’s tunable conductivity is varied by a DC voltage. This in turn causes a reactance variation at the input of the tapered line, which causes a phase variation. The physical parameters of the stubs are optimized for a maximum reactance variation by the help of analytical models, circuit and full wave simulations. Measurements of an optimized prototype are performed and a dynamic phase variation of <semantics>59∘</semantics> is obtained with an amplitude variation of less than 1 dB.